2020
DOI: 10.23960/jpp.v10.i2.202004
|View full text |Cite
|
Sign up to set email alerts
|

Do School Climate and Subjective Well-Being Affect Student Achievement in Indonesia?: A Linear Regression Analysis

Abstract: Do school climate and subjective well-being affect student achievement in Indonesia? A linear regression analysis. Objectives: The purpose of this study is divided into two parts. First, to investigate whether school climate and subjective well-being influence student achievement. Second, to determine whether school size moderates this association, especially the teacher support and student achievement. Methods: This research uses a quantitative approach with multiple linear regression analysis techniques. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The results of Wibowo et al's research in 2020 show that the school climate has a positive impact on the academic achievement of junior high school students in Indonesia (19). The results of the research by Hultin et al, stated that school climate has a positive correlation with the academic achievement value of junior high school students in Swedia (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Wibowo et al's research in 2020 show that the school climate has a positive impact on the academic achievement of junior high school students in Indonesia (19). The results of the research by Hultin et al, stated that school climate has a positive correlation with the academic achievement value of junior high school students in Swedia (20).…”
Section: Resultsmentioning
confidence: 99%
“…Salle 2018 measures student academic achievement into 4 indicators, namely student safety, school environmental conditions, peer and adult relationships, and learning activities (29). Wibowo 2020 measures student academic achievement with indicators of the relationship between students, staff and teachers, safety during teaching and learning process, and the atmosphere of the school environment (19). Thapa & Cohen in 2013 measured student academic achievement with 5 indicators, namely student safety, relationships between school members, the learning process, the organizational environment, and the school improvement process (30).…”
Section: Resultsmentioning
confidence: 99%
“…Riedel et al (2020) explained that redesigning lessons and learning contexts to make schools more interesting can help improve well-being. Based on the research of (Wibowo et al, 2020) it was found that engagement, positive emotion, and peer support had a positive effect on student achievement in Indonesia. It was further strengthened by the argument on the importance of implementing positive education in schools.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Program for International Student Assessment (PISA) in 2018 show that Indonesia's reading scores ranked 72 out of 77 countries, math scores ranked 72 out of 78 countries, and science scores ranked 70 out of 78 countries, indicating that there are problems in the education system in Indonesia (Wibowo et al, 2020). Although the ministry of education and culture has done various ways to improve student achievements such as changes and revisions of the curriculum to adjust it to the market demand, research results show that Indonesia's achievements over the past ten years have not increased (Pratiwi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…So that [16] can explain the benefits of positive education significantly, It is important for schools to consider the best way to develop and support the well-being of their students [17] also suggested a redesign in the context of learning so that the learning process and schools become interesting and help improve welfare. Based on research [18] it was found that engagement, positive emotion, and peer support have a positive effect on student achievement in Indonesia. So that it can be seen the importance of implementing this positive education in Indonesia.…”
Section: Issn: 2716-4160 mentioning
confidence: 99%